Strategies Used by English Second Language Teachers to Cope with Teaching Challenges - Isidor Haufiku; Percy Mashebe; James Abah (ELE Reviews: English Language Education Reviews, 2023)
The main aim of the study is to investigate the strategies used by English Second Language (ESL) teachers to cope with their specific teaching challenges in Senior Secondary Schools in Ohangwena Region, Namibia. The study used the phenomenological qualitative research design to collect data from a purposively selected sample of 33 ESL teachers who have taught for at least two years in the Ohangwena Region. Data were collected using focus group discussions and analyzed using the thematic analysis method. The study found that ESL teachers in Ohangwena Region mainly use strategies such as motivating learners, a learner-centered teaching approach, a group work teaching approach, teachers’ teamwork, and different sources of teaching materials to cope with their respective teaching challenges. While the coping strategies teachers use have been reported to be helpful in ESL teaching, there is still a need to build the teachers’ capacity on the good practices in using such strategies to mitigate their teaching challenges.